Spatial discrimination is abnormal in focal hand dystonia - Bara-Jimenez, W; Shelton, P; Hallett, M (Neurology, 2000)
In patients with focal hand dystonia, abnormal digit representations in the primary somatosensory cortex (S1) could be the result of enlarged and overlapping receptor fields, as suggested by an animal model of dystonia. A possible clinical correlate of this S1 abnormality is a disturbed spatial discrimination capability. To test the hypothesis that somatosensory spatial discrimination is abnormal in focal hand dystonia. Seventeen patients with focal hand dystonia underwent a quantitative evaluation of somatosensory spatial frequency (gap detection, JVP domes, applied to the distal phalanx of the index finger) and single-touch localization (Von Frey monofilaments, applied to the middle phalanx of the index finger). Compared with control subjects, patients had a decreased performance in both the gap detection (p = 0.004) and the localization (p = 0.013) tasks. The extent of spatial frequency abnormality correlated with age in both groups. These findings, together with a previously shown temporal discrimination deficit, support a role for sensory dysfunction in the pathophysiology of dystonia.